A transcriptome-wide identification of ATP-binding cassette (ABC) transporters revealed participation of ABCB subfamily in abiotic stress management of Glycyrrhiza glabra L - Ritu Devi; Pooja Goyal; Bhawna Verma; Shahnawaz Hussain; Fariha Chowdhary; Palak Arora; Suphla Gupta (BMC Genomics, 2024)
Abstract Transcriptome-wide survey divulged a total of 181 ABC transporters in G. glabra which were phylogenetically classified into six subfamilies. Protein–Protein interactions revealed nine putative GgABCBs (-B6, -B14, -B15, -B25, -B26, -B31, -B40, -B42 &-B44) corresponding to five AtABCs orthologs (-B1, -B4, -B11, -B19, &-B21). Significant transcript accumulation of ABCB6 (31.8 folds), -B14 (147.5 folds), -B15 (17 folds), -B25 (19.7 folds), -B26 (18.31 folds), -B31 (61.89 folds), -B40 (1273 folds) and -B42 (51 folds) was observed under the influence of auxin. Auxin transport-specific inhibitor, N-1-naphthylphthalamic acid, showed its effectiveness only at higher (10 µM) concentration where it down regulated the expression of ABCBs, PINs (PIN FORMED) and TWD1 (TWISTED DWARF 1) genes in shoot tissues, while their expression was seen to enhance in the root tissues. Further, qRT-PCR analysis under various growth conditions (in-vitro, field and growth chamber), and subjected to abiotic stresses revealed differential expression implicating role of ABCBs in stress management. Seven of the nine genes were shown to be involved in the stress physiology of the plant. GgABCB6, 15, 25 and ABCB31 were induced in multiple stresses, while GgABCB26, 40 & 42 were exclusively triggered under drought stress. No study pertaining to the ABC transporters from G. glabra is available till date. The present investigation will give an insight to auxin transportation which has been found to be associated with plant growth architecture; the knowledge will help to understand the association between auxin transportation and plant responses under the influence of various conditions.